2021
DOI: 10.3991/ijoe.v17i09.25205
|View full text |Cite
|
Sign up to set email alerts
|

WILD HOPPER Prototype for Forest Firefighting

Abstract: In Europe, fire represents an important issue for a lot of researchers due to economic losses, environmental disasters, and human death. In the last decade, the European parliament sheds light upon this problem by dealing with the community project” Forest Focus”. Thus, researchers and scientific research departments of European companies begin to work on solving and creating different techniques to deal with such a problem, these research centers found that the most attractive and accurate way of solving such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In this paper, a novel approach is put forth that, despite its rarity in the history of aeronautics, if constructed properly, may stabilize an unmanned aerial vehicle (UAV) for a long period, even in the presence of wind disturbances. More literature reviews could be found in authors’ previous works [ 11 , 12 , 13 , 14 , 15 , 16 ]. Briefly, the control strategy presented in this paper—thrust vectoring using flap vanes—offers various advantages over other strategies, including simplicity of servo installation and reduction in the mechanical complexities compared to those of collective pitch propellers because they have fewer movable components; more dynamic stability in attitude control, rather than rotatable hinges or ducts; more efficiency in lift generation based on flap design, as opposed to collective pitch props, which also offer faster response times, and when adjusting the flow direction and magnitude, allows for rapid changes in thrust vectoring, which can be advantageous for applications requiring agile flight control [ 17 ]; and finally, properly designed flap vanes can contribute to noise reduction.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, a novel approach is put forth that, despite its rarity in the history of aeronautics, if constructed properly, may stabilize an unmanned aerial vehicle (UAV) for a long period, even in the presence of wind disturbances. More literature reviews could be found in authors’ previous works [ 11 , 12 , 13 , 14 , 15 , 16 ]. Briefly, the control strategy presented in this paper—thrust vectoring using flap vanes—offers various advantages over other strategies, including simplicity of servo installation and reduction in the mechanical complexities compared to those of collective pitch propellers because they have fewer movable components; more dynamic stability in attitude control, rather than rotatable hinges or ducts; more efficiency in lift generation based on flap design, as opposed to collective pitch props, which also offer faster response times, and when adjusting the flow direction and magnitude, allows for rapid changes in thrust vectoring, which can be advantageous for applications requiring agile flight control [ 17 ]; and finally, properly designed flap vanes can contribute to noise reduction.…”
Section: Introductionmentioning
confidence: 99%
“…These features have made UAVs a powerful system used in civilian and military applications. In addition, multiple professional solutions are offered by single-UAV systems [ 1 ], and swarms and multi-agent techniques are a line of research that is increasingly gaining the interest of researchers in the last decade due to its high performance in terms of time efficiency, flexibility, and fault tolerance [ 2 ].…”
Section: Introductionmentioning
confidence: 99%